Analysis of Income from Mujair Fish (Oreochromis Massambicus) Cultivation in Tarpon Ponds (Biofloc) (A Case Study of Biofloc Business in Matungkas Village, Minut Regency) - Kaunang, Stella T.; Kumentas, Veronicha; Polan, Threis S.; Ompi, Medy (Green Publisher Indonesia, 2023)
This research investigates the economic viability of tilapia fish farming utilizing the pond liner method (biofloc) in Matungkas Village, Dimembe Subdistrict, North Minahasa Regency, Indonesia. With the agricultural, animal husbandry, and fisheries sectors playing pivotal roles in supporting Indonesia's economy, the study focuses on the freshwater fisheries potential, particularly tilapia, in North Minahasa. The research delves into the innovative use of biofloc technology, analyzing its benefits such as minimal water and land requirements, efficient feed utilization, and waste conversion into fish feed. Mr. Ronny Lensun's tilapia fish farming business, employing the pond liner method, is examined. Despite the region's rich natural resources, the income calculation method used by the owner is identified as simplistic. The study employs quantitative methods to perform a comprehensive income analysis, considering revenue, production costs, and financial metrics. Results demonstrate the profitability of Mr. Ronny Lensun's business, with a break-even point at a selling price of IDR 1,167,807.9 and a production volume of 33.36 kg. The Revenue Cost Ratio (R/C) is calculated at 1.85, indicating the business's sustainability and profitability. The literature review encompasses the biofloc technology and business analysis, emphasizing its advantages in water quality maintenance, organic matter decomposition, and feed efficiency. The study contributes to understanding the economic feasibility of tilapia fish farming with the biofloc method, suggesting potential for wider adoption and development in the region.